MSALSA - a method of positioning search results in music information retrieval systems. (2016) - Mazur, Zygmunt; Wiklak, Konrad
The article describes a modification of the SALSA results ranking algorithm. An assessment of its suitability for the use in a music information retrieval system has been made. The authors propose MSALSA algorithm which uses existing connections (links) between websites and music files. By using these connections, a new method of creating a ranking for music search engine results, independent from the user query, has been developed.